Pengaruh Good Corporate Governance dan Leverage Terhadap Kinerja Keuangan Perusahaan - Misfalah, Khoiri Adha; Adi, Suyatmin Waskito (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Financial performance is one form of assessment with the principle of benefits and efficiency in the use of financial budgets, the financial performance of a company can be obtained from the information presented in financial reports in a period, not only seen from the development of stock prices. The company's performance can be measured using Tobin's return on equity and return on assets. This study aims to examine the effect of good corporate governance and leverage on the company's financial performance. The research approach used in this study is to use the associative method with a quantitative approach. The Data used in this study were obtained from the official website of the Indonesia Stock Exchange regarding the annual reports of banking sub-sector companies in 2020-2022. The population in this study is banking companies listed on the IDX for the period 2020-2022. Sample selection in this study using purposive sampling method. The results of this study can be concluded that the board of Commissioners, audit Committee, Board of Directors has no effect on financial performance, while leverage has a significant effect on financial performance.